Influence of filler-binders on ibuprofen iablets with direct compression method - Hadisoewignyo, Lannie; Teny, Gracesya Florensya; Handayani, Elok Tri; Yunita, Beby (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Ibuprofen is a active ingredient that have low melting point, but it has poor flowability, and poor compactibility, this causes ibuprofen tablets are not suitable to be made by direct compression method. The use of appropiate filler-binders can improved the flow properties and compactibility powder that can be made by direct compression. Filler binders commonly use are Avicel PH 102, Emcompress, SDl, and Starch 1500. Formula tablet ibruprofen using Avicel PH 102 as filler-binder will produce tablet with good hardness, low friability, fast disintegrating, and high dissolution. This is because the hydrophilic properties and plastic deformation which is owned by Avicel PH 102.Key words:Ibuprofen, Avicel PH 102, direct compression